Measuring influence in the family decision making process - Lau, Teck Sien (2014)
Family Consumer Research is an area that has attracted a lot of research attention and effort from academics and marketers. However, the emphasis has been largely on the influence of spouses. Hence, most research studies have neglected the role children play in family decisions. The degree and nature of children's influence in family decision making have not been satisfactorily established. The purpose of this report is to research and further extend the present body of knowledge in this area.